Pengaruh Customer Relationship Management dan Servicescape Terhadap Kepuasan Konsumen Produk KFC (Studi Kasus Pada SMA St Yoseph Medan) - Sirait, Yosi Irma Liza; Tarigan, Eka Dewi Setia (Mahesa Research Center, 2024)
This research aims to determine the influence of customer relationship management and servicescape on KFC consumer satisfaction (case study at St Yosep High School, Medan). This research uses quantitative methods. The sample in this study was 81 St Joseph High School students. Data collection was carried out by distributing questionnaires. Data analysis in this study used SPSS 25. The research results show that customer relationship management has a positive effect on KFC consumer satisfaction, this is proven by the t-count value of 2.311, which is significant of 0.022. Servicescape has a positive and significant effect on KFC consumer satisfaction, this is proven by the t value of 5.567 and a significant value of 0.000. customer relationship management and servicescape are simultaneously significant to KFC consumer satisfaction, this is proven by the Fcount value of 114,958 and is significant of 0.000.